Down syndrome burden in China and globally: a comparative analysis of 1990–2021 trends and future projections based on GBD 2021 database - Tu, Xiangwen; Zhang, Feng; Chen, Junkun; Tang, Manmei (Frontiers in Public Health, 2025)
BackgroundDown syndrome (DS), a neurodevelopmental disorder caused by a chromosomal abnormality, poses a major burden on global health. Analyzing the disease burden of DS, both in China and globally, is crucial for refining public health strategies.MethodsUsing the Global Burden of Disease (GBD) 2021 database, we examined age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life year rate (ASDR) for DS in China and globally from 1990 to 2021. Joinpoint regression analysis was applied to identify temporal trends by calculating the annual percent change (APC) and average annual percent change (AAPC). A bayesian age-period-cohort (BAPC) model was further employed to project prevalence changes from 2022 to 2036.ResultsFrom 1990 to 2021, China’s ASIR decreased from 1.68 per 100,000 to 1.18 per 100,000, compared to a global reduction from 1.27 per 100,000 to 0.97 per 100,000. Similarly, ASPR in China fell from 28.01 per 100,000 to 24.8 per 100,000, while globally it dropped from 27.98 per 100,000 to 21.07 per 100,000. Notably, China experienced steeper declines in ASMR (EAPC = −4.18%) and ASDR (EAPC = −3.87%) compared to the global averages (−0.44% and −0.69%, respectively). Joinpoint regression analysis shows that from 1990 to 2021, China’s ASIR (AAPC = −1.15, p < 0.001), ASPR (AAPC = −0.39, p < 0.001), ASDR (AAPC = −2.87, p < 0.001), and ASMR (AAPC = −3.08, p < 0.001) for DS all decreased. The SDI was negatively correlated with ASMR (R = −0.68, p < 0.001) and ASDR (R = −0.66, p < 0.001) but positively associated with ASIR (R = 0.55, p < 0.001) and ASPR (R = 0.80, p < 0.001). Projections from the BAPC model suggest that the ASPR of DS will continue to decline both in China and globally through 2036.ConclusionFrom 1990 to 2021, the disease burden of DS declined in China and globally. China’s decline in ASMR and ASDR outpaced the global level, though ASIR and ASPR remained higher. To further reduce DS burden, future efforts should prioritize early identification, counseling for informed decision-making, and equitable access to quality lifelong multidisciplinary support for affected individuals.